Spectroscopic characterization of rosella flower extract (Hibiscus sabdariffa L.) and its antibacterial activity against Enterobacter aerogenes in suspected typhoid cases - Siti Rohani; Fadhil Rizki Martha; Trisnawati Mundijo; Yesi Astri; Malika Zilda; Agnes Melianti (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2025)
Typhoid, a serious bacterial disease, has spurred research into natural products like rosella (Hibiscus sabdariffa L.) for potential treatments. This study investigates the chemical components found in Rosella extract using spectroscopy approximation, assisted by Fourier transform infrared spectroscopy (FTIR) and Gas chromatography–mass spectrometry (GC–MS). The antibacterial activity of rosella extract on bacteria from stool cultures of suspected typhoid cases continues to be evaluated. The antibacterial experimental employed a post-test-only control group design, using 30 μg Chloramphenicol as a positive control, sterile distilled water as the negative control, rosella extract at concentrations of 25%, 50%, 75%, and 100% as the observed variable. Stool samples from typhoid patients were identified, and Enterobacter aerogenes were detected using VITEK®2 testing. Cultivated bacteria from the samples were tested to determine the antibacterial activity of the rosella extract. Phytochemical studies confirmed the presence of tannins, alkaloids, flavonoids, and saponins in the rosella extract. Additionally, the spectroscopic evaluation from FTIR and GC-MS showed the presence of chemical groups, including esters, aldehydes, and aromatics. Further clinical tests demonstrated antibacterial activity at the minimum inhibitory concentration. The results showed an increasing inhibition zone of bacterial growth, correlating with the increase in rosella extract concentration. Although the antibacterial activity of rosella extract was lower compared to commercial Chloramphenicol, this natural product has demonstrated antibacterial activity and shows potential as a candidate for future herbal medicine development.